Genome Analysis Traces Regional Dispersal of Rice in Taiwan and Southeast Asia. (8th July 2021) - Alam, Ornob; Gutaker, Rafal M; Wu, Cheng-Chieh; Hicks, Karen A; Bocinsky, Kyle; Castillo, Cristina Cobo; Acabado, Stephen; Fuller, Dorian; d'Alpoim Guedes, Jade A; Hsing, Yue-Ie; Purugganan, Michael D
Abstract: The dispersal of rice ( Oryza sativa ) following domestication influenced massive social and cultural changes across South, East, and Southeast (SE) Asia. The history of dispersal across islands of SE Asia, and the role of Taiwan and the Austronesian expansion in this process remain largely unresolved. Here, we reconstructed the routes of dispersal of O. sativa ssp. japonica rice to Taiwan and the northern Philippines using whole-genome resequencing of indigenous rice landraces coupled with archaeological and paleoclimate data. Our results indicate that japonica rice found in the northern Philippines diverged from Indonesian landraces as early as 3, 500 years before present (BP). In contrast, rice cultivated by the indigenous peoples of the Taiwanese mountains has complex origins. It comprises two distinct populations, each best explained as a result of admixture between temperate japonica that presumably came from northeast Asia, and tropical japonica from the northern Philippines and mainland SE Asia, respectively. We find that the temperate japonica component of these indigenous Taiwan populations diverged from northeast Asia subpopulations at about 2, 600 BP, whereas gene flow from the northern Philippines had begun before ∼1, 300 BP. This coincides with a period of intensified trade established across the South China Sea. Finally, we find evidence for positive selection acting on distinct genomic regions in different rice subpopulations, indicating local adaptation associated with the spread of japonica rice.